2014
DOI: 10.1007/s10120-014-0365-z
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle loss after total gastrectomy, exacerbated by adjuvant chemotherapy

Abstract: Background Skeletal muscle loss is associated with physical disability, nosocomial infections, postoperative complications, and decreased survival. Preventing the loss of skeletal muscle mass after gastrectomy may lead to improved outcomes. The aims of this study were to assess changes in skeletal muscle mass after total gastrectomy (TG) and to clarify the clinical factors affecting significant loss of skeletal muscle after TG. Patients and methods One hundred and two patients undergoing TG for primary gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…Previous studies have reported on changes in skeletal muscle mass during chemotherapy in patients with unresectable colorectal cancer [16] and advanced lung cancer [19], changes in skeletal muscle and adipose tissue in gastric cancer patients undergoing total gastrectomy [18] and changes in muscle, fat and bone mass during androgen blockade in prostate cancer patients [17, 26]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported on changes in skeletal muscle mass during chemotherapy in patients with unresectable colorectal cancer [16] and advanced lung cancer [19], changes in skeletal muscle and adipose tissue in gastric cancer patients undergoing total gastrectomy [18] and changes in muscle, fat and bone mass during androgen blockade in prostate cancer patients [17, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…The PNI was calculated using the following formula: 10 × serum albumin (g/dl) + 0.005 × total lymphocyte count (per mm 3 ) [18]. The CONUT score was determined on the basis of the serum albumin, peripheral lymphocyte count and the T-cholesterol, as previously described (Table 1) [22].…”
Section: Methodsmentioning
confidence: 99%
“…In gastric cancer, preoperative sarcopenia has been shown to be a predictive marker of postoperative complications and poor prognosis (9). In two previous studies, a 6.2% loss of skeletal muscle was observed after total gastrectomy (10), and adjuvant chemotherapy with S-1 was identified as an independent risk factor for significant loss of skeletal muscle (11). Moreover, reductions of lean body muscle mass after gastrectomy has been reported to prevent the continuation of adjuvant chemotherapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…The loss in muscle mass actually had no impact on survival in the Osaka study [3]. However, patients who received S-1 monotherapy for more than 6 months should have benefited from adherence to the treatment, given that the standard of care is to deliver S-1 for 12 months.…”
mentioning
confidence: 90%
“…These findings prompted physicians to consider early postoperative enteral nutrition to minimize the inevitable weight loss following gastrectomy, and several trials to prove the benefit of such approach are currently ongoing. In the meantime, another active group of investigators in Osaka reported in a recent article published in Gastric Cancer that a group of patients who tolerated adjuvant S-1 monotherapy for 6 months or more after receiving total gastrectomy carry a significant risk for greater than 10 % loss of skeletal muscle when compared with those who failed to do so [3]. In contrast, the duration of chemotherapy did not affect the degree of loss in total body weight or fat mass.…”
mentioning
confidence: 99%